2015
DOI: 10.1186/s12906-015-0966-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pharmaceutical formulations containing thyme on carbon tetrachloride-induced liver injury in rats

Abstract: BackgroundHerbal supplements are widely used in the treatment of various liver disases, but some of them may also induce liver injuries. Regarding the infuence of thyme and its constituents on the liver, conflicting results have been reported in the literature. The objective of this study was to examine the influence of two commonly used pharmaceutical formulations containing thyme (Thymus vulgaris L.), tincture and syrup, on carbon tetrachloride-induced acute liver injury in rats.MethodsChemical composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…This is also in good correlation with already published study (Ko et al, 2014), which showed significant decrease in a dosedependent manner in the cisplatin and PYC groups, compared with GPx level in septic rats (Taner et al, 2014). However, our result is comparable with similar studies (Rašković et al, 2015) where it was confirmed that APAP induced increase of GPx activity. Actually, under oxidative stress condition, upregulation of GPx can occur as an adaptive response of hepatocytes to oxidative damage, when GSH is largely consumed, which is in agreement with the results of our research (Rašković et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…This is also in good correlation with already published study (Ko et al, 2014), which showed significant decrease in a dosedependent manner in the cisplatin and PYC groups, compared with GPx level in septic rats (Taner et al, 2014). However, our result is comparable with similar studies (Rašković et al, 2015) where it was confirmed that APAP induced increase of GPx activity. Actually, under oxidative stress condition, upregulation of GPx can occur as an adaptive response of hepatocytes to oxidative damage, when GSH is largely consumed, which is in agreement with the results of our research (Rašković et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also revealed that the protective effects of Thyme leave extracts were dose dependent as 20 mg/kg had the highest liver protective effect. High concentrations of Thyme have been reported to cause cytotoxicity and liver damage through generation of ROS (18). Difference among the results might be due to Thyme species and Thyme formulated types.…”
Section: Discussionmentioning
confidence: 90%
“…The identification, quantification, and characterization of phytocomponents from fractionated leaf extracts of A. occidentale, P. guajava, and T. catappa were carried out using standard chromatographic-spectrophotometric protocols, viz. GC-MS systems {Agilent 7890A GC system set up with 5975C VL MSD, Agilent Technologies, Inc., Santa Clara, CA, USA; The MS system was accomplished in Electron Ionization (EI) mode with Selected Ion Monitoring (SIM)}as well as FT-IR and UV-visible instruments (PerkinElmer Spectrophotometer, USA) according to the methods previously described [48,54,55]. The capillary column specification of the GC system was DB-5MS (30 m × 0.25 mm, film thickness of 0.25 μm) with a temperature program set as follows: initial temperature 50°C held for 1.00 min, 5°C per min to 100°C, 9°C per min to 200°C held for 7.89 min, and the total run time was 30 min.…”
Section: Spectrometrymentioning
confidence: 99%
“…Spectrometric methods, viz. Fourier transform-infrared spectroscopy (FT-IR) and ultraviolet-visible spectroscopy (UV-visible) complement gas chromatography-mass spectroscopy (GC-MS) protocols in terms of providing comprehensive insights into the molecular characteristics and quantification of phytocomponents from plant materials [21,[45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%